CORRELATION, ALTERATION, AND ORIGIN OF HYDROCARBONS IN THE GCA, BAHAR, AND GUM ADASI FIELDS, WESTERN SOUTH CASPIAN BASIN: GEOCHEMICAL AND MULTIVARIATE STATISTICAL ASSESSMENTS - Gürgery K. (My University, 2003)
Geochemical as well as multivariate statistical analyses (PCA) were carried out on 20 crude oil samples from ‘Middle’ Pliocene Production Series (MPPS) of Guneshli-Chirag-Azeri (GCA), Bahar, and Gum Adasi fields in the western South Caspian Basin (SCB). PCA analysis employed to source-specific biomarkers distinguishes the oils into two types one being divided into two sub-types; Type 1 (GCA oils), Type 2A (Bahar field oils) and Type 2B (Gum Adasi field oils). Indirect oil-to-source rock correlations to available source rock data from previous studies suggest that Type 1 oils, located in the Apsheron-Balkhans uplift area, are derived from basinal shales of the Oligocene-Lower Miocene Middle Maikop Formation. Type 2A and 2B oils, located in the Gum-deniz-Bahar-Shakh-deniz trend area, are more likely derived from shelf-edge shales of the Upper Maikop Formation and the Middle-Upper Miocene Diatom Suite, respectively.
Keywords: Azerbaijan; Alteration; Biomarker; Correlation; Oil; Maturation; South Caspian Basin